STEAM-H to Support Agribusiness Students' Work Skill - Fatimah, Ai Tusi; Isyanto, Agus Yuniawan; Erlin, Euis (Universitas Muhammadiyah Surakarta, 2024)
The study focuses on the importance of work skills for students at Agribusiness Vocational High Schools in meeting the demands of 21st-century competencies. It explores how the STEAM-H (Science, Technology, Engineering, Agriculture, Mathematics, Health) approach can assist in developing these work skills. The research aims to assess students' grasp of the STEAM-H concept and to identify the work skills they acquire through learning that incorporates the STEAM-H approach. This investigation adopts a case study design involving 16 eleventh-grade students from the Agribusiness Vocational High School for Agricultural Product Processing in Ciamis Regency. Data was gathered through initial and final tests to gauge the students' understanding of STEAM-H, as well as through observations and interviews conducted while the students were engaged in a project on chicken wonton processing to evaluate their work skills. The results indicated a significant improvement in students' comprehension of the STEAMH concept after participating in the learning process. This increased understanding corresponded with the students' work skills, as evidenced by their successful completion of the chicken wonton processing project. The study concludes that the STEAM-H approach holds substantial potential for enhancing students' understanding of mathematics, food security, science, health, and technology concepts relevant to the agribusiness sector while also fostering the development of essential work skills required in the workplace. Wonton production requires a strong interdisciplinary approach. Mathematics, especially computational thinking skills, are crucial in designing an efficient and effective production process. The implication of this study underscores the importance of integrating the STEAM-H approach into the curriculum of Agribusiness Vocational High Schools, thereby preparing students to become competent graduates equipped to confront challenges in the era of Industry 4.0.